Risk of Motor Vehicle Collision or Driving Impairment After Traumatic Brain Injury: A Collaborative International Systematic Review and Meta-Analysis. Issue 1 (January 2019) - Chee, Justin N.; Hawley, Carol; Charlton, Judith L.; Marshall, Shawn; Gillespie, Ian; Koppel, Sjaan; Vrkljan, Brenda; Ayotte, Debbie; Rapoport, Mark J.
Abstract : Objective: To synthesize knowledge of the risk of motor vehicle collision (MVC) following a traumatic brain injury (TBI) and the associated risk of driving impairment, as measured by on-road tests, computerized simulators, and self-reported or state-recorded driving records. Methods: Our international team searched 7 databases for studies published between 1990 and 2015 of people with TBI, controls, and data concerning either MVC or driving impairment. The included articles examined the risk of MVC among people with TBI; we excluded studies that examined the risk of having a TBI associated with being involved in an MVC. Results: From 13 578 search results, we included 8 studies involving 1663 participants with TBI and 4796 controls. We found no significant difference in the risk of MVC (odds ratio = 1.24, 95% confidence interval = 0.80-1.91, P = .34). When we restricted the analysis to self-report, the risk of MVC was higher for those without a TBI (odds ratio = 1.63, 95% confidence interval = 1.21-2.22, P = .002). In contrast, participants with TBI consistently performed worse during on-road assessments and had more problems with vehicular control. Conclusion: Limitations of reviewed studies included small sample sizes, failure to specify TBI severity or time postinjury, and absence of objective measures of risk. Findings concerning the relationship between TBIs from non-MVC causes and crash risk are, therefore, inconclusive and do not provide evidence for major changes to existing clinical guidelines for driving with TBI. Abstract : Supplemental Digital Content is Available in the Text.